Analysis of the Level of Understanding of the Binjai City Public Towards the Use of Non-Cash Payments - Seprianti, Viola Ditya; Lubis, Irsad (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
Along with the rapid development of technology, the transformation of the payment system is also growing, especially in terms of non-cash payment systems. Considering that this payment system is one of the important components in the world economy and is also a work program of Bank Indonesia in order to improve the non-cash payment system to achieve better economic growth. This study aims to determine the level of understanding and benefits of non-cash payments on the use of non-cash payments in Binjai City. This study uses primary data obtained by distributing questionnaires and interviews. This study is a descriptive statistical study with a sample of 100 respondents in Binjai City. The results of the study Understanding of non-cash payments from respondents in the study have an effect on the use of non-cash payments such as electronic money or APMK in Binjai City. The benefits of non-cash payments from respondents in the study have an effect on the use of non-cash payments such as electronic money or APMK in Binjai City.